Manajemen Strategi Pencegahan Penyalahgunaan Narkotika Di Badan Narkotika Nasional Kabupaten Kuantan Singingi (Studi Kasus Pada Kalangan Remaja) - Fajri Hidayah Erza; Abdul Sadad (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2022)
The strategy in preventing the circulation of narcotics is one form of performance carried out by the National Narcotics Agency and in collaboration with various government agencies, non-government institutions and also the community in preventing narcotics trafficking in Kuantan Singingi Regency which is experiencing a high level of narcotics circulation, resulting in many drug users, especially in among teenagers. This study aims to determine how the Strategy of the National Narcotics Agency of Kuantan Singingi Regency in the Prevention of Narcotics Abuse among Adolescents. This research is descriptive qualitative by using secondary data collection techniques by conducting library research and other secondary data sources as well as conducting direct research to the field to obtain primary data through observation, documentation, and interviews. In this study, researchers used the theory of J. David Hunger and Thomas L. Wheelen (2003: 3) which consists of 4 components, namely; Environmental Observation, Strategy Formulation, Strategy Implementation, and Evaluation and Control. The results of the study show that in carrying out efforts to prevent the National Narcotics Agency of Kuantan Singingi Regency, it has not run optimally due to the lack of information dissemination or socialization carried out by P2M to adolescents in Kuantan Singingi Regency, then the lack of public awareness of adolescent drug abusers, and human resources that are still lacking. so that it affects efforts to prevent drug abuse in adolescents in Kuantan Singingi district.